Editorial of the Special Issue on Following User Pathways: Key Contributions and Future Directions in Cross-Platform Social Media Research. Issue 10 (3rd October 2018) - Hall, Margeret; Mazarakis, Athanasios; Chorley, Martin; Caton, Simon
ABSTRACT: Social media and the resulting tidal wave of the available data have changed the ways and methods researchers analyze communities at scale. But the full potential for social scientists (and others) is not yet achieved. Despite the popularity of social media analysis in the past decade, few researchers invest in cross-platform analyses. This is a major oversight as a majority of online social media users have multiple social media accounts. Missing are the models and tools necessary to undertake analysis at scale across multiple platforms. Especially promising in support of cross-platform analysis is the mixed-method approach (e.g., qualitative and quantitative methods) in order to better understand how users and society interact online. This special issue "Following User Pathways" addresses methodological, analytical, conceptual, and technological challenges and opportunities of cross-platform analysis in social media ecosystems.